Internet marketing organization with the use of intellegent and block chain technologies - U. A. Vishniakou (Системный анализ и прикладная информатика)
The purpose of this work is to analyze methods, approaches, technologies, and means of Internet marketing (IM), using both known technologies and developing new ones: intellectual and blockchain. The objectives of the analysis are to identify trends in the development of Internet marketing in the digital economy with the use of intelligent and blockchain technologies, and to develop new structural solutions.The analysis of the use of intelligent technologies in marketing activities (MA) using cloud computing (CC) is carried out and its features are determined. Proposals have developed for improving Internet marketing in an integrated environment (traditional network and cloud one) using intelligent and blockchain technologies. It is proposed to develop IA on the basis of a family of intelligent agents for building intelligent marketing information systems (IMIS). The use of blockchain technology in IM for controlling resources and marketing operations is shown. A new concept for the development of IM and IIMS is presented, on the basis of which approaches to the organization of IMIS for communication between enterprises, research institutes and universities are developed. The structure of an intelligent portal based on multi-agent technology that unites developers and consumers of startups has been developed. Blockchain technology is used to control and guarantee the authorship of startups and signed contracts.As IM development trend, the development of models for joint activity of intelligent agents in the cloud environment to support decision-making using blockchain technology to legally secure the authorship of innovations is proposed. There are two areas of development of intelligent marketing systems: adaptation in digital markets and support for innovative activities with the consolidation of contracts based on blockchain technology.